2016
DOI: 10.1084/jem.20151720
|View full text |Cite
|
Sign up to set email alerts
|

Bridging channel dendritic cells induce immunity to transfused red blood cells

Abstract: Calabro et al. show that 33D1+ dendritic cells present in the bridging channel of the spleen are essential for alloantibody response to transfused red blood cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
114
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(126 citation statements)
references
References 39 publications
12
114
0
Order By: Relevance
“…10 In agreement with these findings, the splenic T cell subsets were shown to be pivotal for antibody production against both autologous and allogeneic platelet membrane antigens.…”
Section: Letters To the Editorsupporting
confidence: 53%
“…10 In agreement with these findings, the splenic T cell subsets were shown to be pivotal for antibody production against both autologous and allogeneic platelet membrane antigens.…”
Section: Letters To the Editorsupporting
confidence: 53%
“…In addition to expression of co-stimulatory molecules, a balanced release of cytokines and chemokines by DC is also crucial for directing multiple immune pathways [93]. I found minimal modulation of cytokine responses following exposure to PRBC alone, however, both mDC and BDCA3 + DC responses to polyI:C and LPS were suppressed in the presence of PRBC.…”
Section: Prbc Storage Was Associated With Increased Erythrophagocytosismentioning
confidence: 92%
“…Erythrophagocytosis by murine plasmacytoid (p)DC particularly in costimulation with TLR3 agonist, polyinosinic-polycytidylic acid (polyI:C)-driven inflammation has been reported [91]. Murine studies have also demonstrated that splenic DC are important for outcomes in terms of alloimmunisation [92,93].…”
Section: In-vitro and In-vivo Models Of Prbc Transfusion (Related To mentioning
confidence: 99%
See 2 more Smart Citations